2017
DOI: 10.1186/s12906-017-1988-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential effectiveness of Chinese herbal medicine Yu ping feng san for adult allergic rhinitis: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundChinese herbal medicine formula Yu ping feng san (YPFS) is commonly used for allergic rhinitis (AR). Previous review had summarized the effectiveness and safety of YPFS, however without any subgroup analysis performed to provide detailed evidence for guiding clinical practice. YPFS was recommended for the management of AR by Chinese medicine clinical practice guideline, but the treatment duration of YPFS was also not specified. The aim of this study is to evaluate the effectiveness and safety of YPFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…A review of one such CHM, Yu ping feng san, identified 22 randomized controlled trials (of 1244 records) with 2309 participants with AR. 557 Control groups included placebo, pharmacotherapy, and the combination of CHM and pharmacotherapy, and the treatment periods ranged from 2 to 8 weeks. Results were limited in the placebo-control trials and suggested a trend for benefit from CHM in a very small number of studies.…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…A review of one such CHM, Yu ping feng san, identified 22 randomized controlled trials (of 1244 records) with 2309 participants with AR. 557 Control groups included placebo, pharmacotherapy, and the combination of CHM and pharmacotherapy, and the treatment periods ranged from 2 to 8 weeks. Results were limited in the placebo-control trials and suggested a trend for benefit from CHM in a very small number of studies.…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…OBPS has shown efficacy against allergic reactions and inflammation and thus has been applied to treat AR, COPD, asthma, and so on. [ 2 , 17 , 18 ] OBPS regulates inflammation processes by both boosting inflammation and suppressing inflammation. In detail, OBPS stimulates mRNA and protein expression of pro-inflammatory cytokines via NF-kB and suppresses mRNA and protein expression in a lipopolysaccharide (LPS)-induced chronic inflammation model.…”
Section: Discussionmentioning
confidence: 99%
“…There was 1 research article that was a systematic review and meta-analysis of RCTs. [ 2 ] This article included 22 RCTs, and OBPS was compared to placebo and pharmacotherapy. However, the study had some limitations, as mentioned in the article itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 – 17 Clinical studies have demonstrated that YuPingFeng powder reduces the risk of recurrent respiratory infections by regulating the immune system, 18 inhibiting inflammatory cytokines in vivo, 19 and by its anti-allergic effects. 20 Therefore, we hypothesized that YuPingFeng granules may be effective in treating COPD.…”
Section: Introductionmentioning
confidence: 99%